Predictors of everyday functional impairment in older patients with schizophrenia: A cross-sectional study - Wu, Chenxin; Ye, Junrong; Li, Shaohua; Wu, Jialan; Wang, Chen; Yuan, Lexin; Wang, Haoyun; Pan, Yuanxin; Huang, Xingxiao; Zhong, Xiaomei; Huang, Meilian; Guo, Jianxiong; et al. (Frontiers in Psychiatry, 2023)
Objective This study investigates the prevalence of everyday functional impairment among older adults with schizophrenia and builds a predictive model of functional decline. Methods A total of 113 hospitalized older patients enrolled in this study. Functional impairment is defined according to the Functional Activities Questionnaire (FAQ). Patients who scored <9 could function independently daily, while those who scored ≥9 had problems in everyday functional activities. Data collected include sociodemographic characteristics, depressive symptoms, social support, and physical comorbidities, which were classified according to the eight anatomical systems of the human body. Results The sample comprised 75% female participants with a mean age of 63.74 ± 7.42 years old. A total of 33.6% had a functional impairment, while cognitive impairment was present in 63.7%. Independent participants had better urinary system and respiratory system health (P < 0.05). After adjusting for the potential confounders of age, disease course, physical comorbidities, psychiatric symptoms, the ability to independently carry out daily activities, and cognitive function, we found that impaired everyday function is associated with poor cognition, depressive symptoms, first admission, psychiatric symptoms (especially positive symptoms), ADL, and respiratory and urinary system diseases. Conclusion Everyday functional capacity is predicted by disease course, admission time, cognition, depressive symptoms, severity of psychosis, ability to carry out daily activities, and respiratory and urinary system health status. Urinary system diseases contribute significantly to the prediction of impaired function. Future studies should focus on health status, drug use, and everyday functional recovery in older patients with schizophrenia.